Bladder traumatic hernia. - Croci, Fabio; Pérez Penco, Ernesto; Rabellino, Joaquín; Tarabochia, Carlos; Pastro, Dante (Cirugía del Uruguay, 1987)
A case of bladder traumatic hernia that apperaed immediately alter a motor vehicle accident is presented. lis origin was the disruption of both rectus abdominis muscles from the pubic junction. Sorne considerations about pathology, diagnosis and therapeutic of traumalíe wall hernia are done.